Pendampingan Pasien GERD (Gastroesophageal Reflux Disease) dalam Upaya meningkatkan Motivasi Penyembuhan Menggunakan Layanan Konseling Individual - Hernisawati Hernisawati; Haikal Haikal (Jurnal Pengabdian Multidisiplin, 2022)
The purpose of this study was to determine how the identification and analysis of psychotherapy on the healing of GERD (Gastrophageal Reflux Disease) patients in terms of using a personal counseling service. GERD is a symptom that usually occurs when stomach acid rises so that the mouth feels sour and bitter as well as a burning or burning sensation in the chest and gut, this condition triggers a psychological situation consisting of anxiety, panic to depression as evidenced by physical conditions, namely shortness of breath, cold sweat and if left untreated it causes the patient's condition to get worse, this proves that motivation for healing is needed. The method used in this research is qualitative research methods. The subjects in this study were GERD patients consisting of IAIMNU Metro Lampung residents. Data collection techniques used in this study were interview techniques and observation techniques. The data in this study were analyzed using qualitative descriptive analysis. Identification and psychological analysis of patients with GERD can be seen that, (a) anxiety due to the risk of disease to the body, (b) panic arising